The Role of Modeling and Simulation in Development and Registration of Medicinal Products: Output From the EFPIA/EMA Modeling and Simulation Workshop. (27th February 2013) - Manolis, E; Rohou, S; Hemmings, R; Salmonson, T; Karlsson, M; Milligan, PA
Abstract : The European Medicines Agency (EMA) and the Federation of Pharmaceutical Industries and Associations (EFPIA) hosted a workshop on modeling and simulation (M&S). 1 Representatives from industry, academia, and regulatory agencies from Europe and beyond discussed the role of M&S in the development and registration of medicinal products within plenary and breakout sessions (BOS). This manuscript summarizes the plenary discussion (Table 1 ) focusing on the European perspective. Deliverables from each BOS are included in separate papers. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e31; doi:10.1038/psp.2013.7 ; advance online publication 27 February 2013